THE QUALITY OF LIFE OF TODDLER POST COLOSTOMY IN BANDUNG - Dede Nurhayati; Ai Mardhiyah; Fanny Adistie (Faculty of Nursing, Universitas Jember, 2017)
Congenital abnormalities in children are still quite high in Indonesia such as hirschsprung disease and anorectal malformations which require the fabrication of colostomy as bowel decompression and faecal expenditure alternatives. Stoma fabrication can have a physical or psychosocial impact on a child's life. This study aimed to determine the perception of parents on the quality of life in toddler-aged children with post colostomy. The method of this research was quantitative descriptive with 35 respondents obtained by consecutive sampling technique. The participants involved in this study were the parents of toddler-aged children who had experienced colostomy surgery. The data were collected using a Pediatric Quality of Life Inventory (Peds QL) questionnaire. The data were analyzed with descriptive statistics. The results showed that 19 people (54.28%) of toddler-aged children who had experienced colostomy surgery had poor quality of life with the lowest score on cognitive function. The conclusions of this study indicated that most of parents perceived the quality of life of toddler-aged children who had experinced colostomy surgery in the bad category. The poor quality of life can affect the child growth. One of the efforts to improve the quality of life of children is by providing psychological therapy to help children deal with negative emotions and providing psychoeducation to parents about the importance of providing stimulus in toddler-aged childern so that children can have a better quality of life.